The effect of omnichannel perceived value and integration toward customer satisfaction: technology readiness as moderator - Daniel Clarence Marthin; Triana Rahajeng Hadiprawoto (President University, 2022)
In recent years, companies within various industries made attempts to transform themselves into omnichannel organizations. In doing so, most companies focus on providing a seamless customer experience which plays a major role in an omnichannel strategy. Previous research has shown that seamless customer experience could affect customer omnichannel journey positively. Furthermore, it builds a strong relationship between customer omnichannel journey and customer behavior. Another research has shown that omnichannel integration quality and omnichannel perceived value could have a positive effect on customer satisfaction. However, there is a lack of omnichannel research specifically regarding the characteristics of customers who engage in an omnichannel environment considering the digitalization era and how customers might navigate interaction with technology differently. Therefore, this paper aims to find out whether customer characteristics, such as technology readiness, are able to moderate the effect between omnichannel perceived value and customer satisfaction. This study uses Partial Least Square to analyze the data from a sample of 200 respondents who have used the omnichannel platform of a particular hospital in Indonesia, specifically a combination of online channels (e.g., website, third party app, hospital mobile app) and an offline channel (visiting hospital directly). The respondents have given a questionnaire consisting of 40 items and a 5-point Likert to examine each item. The result is that perceived value has a positive impact on customer satisfaction as well as integration quality to customer satisfaction. There is also a positive impact on customer satisfaction to customer loyalty.